Substitute for x 2x-3y = 6 x = (6+3y)/2
x = 3/2y +3 = (6+3y)/2 Multiply both sides of the equation by 2y
3 + 6y = 6y +3y^ y^ = 0 y = 0 and x= 3
Proof :- 2x - 3y = 6 i.e. 2 x 3 - 3 x 0 = 6
2006-12-04 03:51:11
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
x-3/2y=3
2x-3y=6
I would use linear combination unless you have studied matricies.
linear combination:
x-3/2y=3 // multiply the top one by -2 and add it to the
2x-3y=6 bottom one to cancel the x
--------------
0=0
when you get an answer that is ALWAYS true (like 0 = 0) the lines are the exact same, if you get a statement that is NEVER true (like 1 = 3) the lines do not intersect. (they must be plaallel and not the same line)
2006-12-04 11:38:50
·
answer #2
·
answered by Scooter_MacGyver 3
·
0⤊
0⤋
2x - 3y = 6
x - 3y/2 = 3
By inspection each equation is the same; hence, you do not have two equations to solve two unknowns. The best you can do is to solve for y:
2x-3y=6
-3y=6-2x
y=-2+2x/3 a straight line
2006-12-04 11:36:48
·
answer #3
·
answered by kellenraid 6
·
1⤊
0⤋
(x - 3/2y = 3
(2x - 3y =6
Equation I: x = 3 + 3/2y
Equation II:
2(3 + 3/2y) - 3y = 6
6 + 3y - 3y = 6
0y = 6-6
It's impossible to solve.
<>>
2006-12-04 11:43:55
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
x=3/2y+3 ------------ equ 1
2x-3y=6 -------------equ2
solution:
2x = 3y + 6
=> x = 3y/2 + 3
sub in equ 1
3y/2 + 3 = 3/2y + 3
cancel 3 on both sides,
3y/2 = 3/2y
cancel 3/2 on both sides
y = 1/y
cross multiplication
y^2 = 1
y = sqrt (1)
y=1 or -1.
if y=1, then x = 3/2 +3 // in equ 1
x=9/2
if y=-1, then x = -3/2 + 3 // in equ 1
x=3/2.
2006-12-04 12:24:46
·
answer #5
·
answered by candy 2
·
0⤊
0⤋
The 1-st and the 2-nd equations are equavalent, so you only have one (no matter which). From one equation you can find how x depends from y (or y from x). so, the answer is
x = x
y = (2/3)*x - 2
Yes, y = (2/3)*x - 2 is straight line , and she is infinite, so there are infinite number of answers.
(Get whatever you want x and put it to equation - you will get y, ans so on).
The answer we can write like that - { x ; (2/3)*x-2 }
2006-12-04 11:47:56
·
answer #6
·
answered by asqwenit 1
·
0⤊
0⤋
It is not possible to solve only one equation with 2 variables.
2006-12-04 11:41:17
·
answer #7
·
answered by Adithya M 2
·
0⤊
0⤋